Combined Effects of Dewatering, Composting and Pelleting to Valorize and Delocalize Livestock Manure, Improving Agricultural Sustainability - Domenico Ronga; Paolo Mantovi; Maria Teresa Pacchioli; Andrea Pulvirenti; Francesco Bigi; Giulio Allesina; Simone Pedrazzi; Aldo Tava; Aldo Dal Prà (Agronomy, 2020)
An agronomic strategy to mitigate climate change impact can be the build-up of soil organic carbon. Among agronomic management approaches, the administration of organic fertilizers like livestock manure represents an effective strategy to increase soil organic carbon. However, livestock manure usually contains a high amount of water, reducing its sustainable delocalization and impacting on greenhouse gas emissions and nutrient leaching. Furthermore, the possible presence of weed seeds and harmful microorganisms could reduce the agronomic value of the manure. To overcome these issues, the combined effects of dewatering, composting and pelleting were investigated on livestock manure to produce sustainable organic fertilizers. Our results showed that composting and pelleting can represent a feasible and sustainable solution to reduce the potential risks related to the presence of weed seeds and harmful bacteria, concentrating nutrients and allowing a sustainable valorization and delocalization of the livestock manure. In addition, the processed manures were assessed as fertilizers in the growing medium (GM), displaying an increase in water retention and nutrient availability and a decrease of GM temperature and weed seed emergences. However, further study is needed to validate, both in open field and greenhouse productions, the effects of the proposed fertilizers in real cropping systems.